Notre-Dame de Paris - Hugo, Victor, 1802-1885 (Oxford world's classics (Oxford University Press), 1999)
This translation of Notre-Dame de Paris offers Victor Hugo's epic view of mankind's history, which assumes even more importance than the novel's compelling story.